Determining the Optimum Tilt Angles to Maximize the Incident Solar Radiation - Case of Study Pristina - Berisha, Xhevat; Zeqiri, Arianit; Meha, Drilon (Center of Biomass & Renewable Energy, Diponegoro University, 2018)
Solar energy is derived from photons of light coming from the sun in a form called radiation. Solar energy finds extensive application in air and water heating, solar cooking, as well as electrical power generation, depending on the way of capturing, converting and distribution. To enable such application, it is necessary to analyze the horizontal tilt angle of horizontal surfaces â€“ in order that when the solar energy reaches the earth surface to be completely absorbed. This paper tends to describe the availability of solar radiation for south-facing flat surfaces. The optimal monthly, seasonal, and annual tilt angles have been estimated for Pristina. The solar radiation received by the incident plane is estimated based on isotropic sky analysis models, namely Liu and Jordan model. The annual optimum tilt angle for Pristina was found to be 34.7Â°. The determination of annual solar energy gains is done by applying the optimal monthly, seasonal and annual tilt angles for an inclined surface compared to a horizontal surface. Monthly, seasonal and annual percentages of solar energy gains have been estimated to be 21.35%, 19.98%, and 14.43%. Losses of solar energy were estimated by 1.13 % when a surface was fixed at a seasonal optimum tilt angle, and when it was fixed at an annual optimum tilt angle, those losses were 5.7%.Article History: Received February 15th 2018; Received in revised form May 12th 2018; Accepted June 2nd 2018; Available onlineHow to Cite This Article: Berisha, Xh., Zeqiri, A. and Meha, D. Â (2018) Determining the Optimum Tilt Angles to Maximize the Incident Solar Radiation - Case of Study Pristina. Int. Journal of Renewable Energy Development, 7(2), 123-130.https://doi.org/10.14710/ijred.7.2.123-130